Factors influencing purchasing decisions of baby care products in the Icelandic market - Alexandra Nicole Franková 1994- (2022)
In regard to babies, manufacturers are continuously researching ways to develop the most state-of-the-art baby care products. Parents and other baby product consumers are concerned with purchasing the best products in the marketplace and doing everything they can to ensure the health and safety of the baby. But how do baby product consumers determine which products are the best and which ones are not going to deliver the value in which they are seeking? Do they merely guess or are they looking carefully, researching the attributes and factors that go in to finding the optimal product for the child they are purchasing for? The aim of this article is to discover what consumer’s priorities are in the Icelandic market when choosing to purchase baby care products and the most influential factors in that decision. The fundamental purpose of this it is to discover how such factors are behind the success of the purchase decision making process. Understanding the consumers' perceptions, behavior and priorities concerning baby care products is an important topic. There is a lack of information about the consumers' perceptions and what factors determining their buying behavior about baby care products in Iceland. This study uses the mixed method exploratory approach, a strategic combination of both qualitative and quantitative research approaches. The targeted sample is parents and other baby product consumers who have the experience of buying baby care products in Iceland. The size of the sample is 305 participants, including fathers, mothers, family, and friends of babies of primarily 0-4 years in age. The participants included are of random selection to collect the most diverse and non-biased data. This includes participants who are both Icelandic and international permanent residents of Iceland. The research is designed as a questionnaire collected in Google Forms, as well as five one-on-one interviews. The results indicated that ingredients of products, environmental concern, price, natural and organic properties of ...